PHOTODEGRADATION OF DIRECT YELLOW 50 DYE USING THE PHOTOCATALYST ZINC OXIDES UNDER ULTRA-VIOLET LIGHT - Mousa, Souad A. (International Journal of Research -GRANTHAALAYAH, 2017)
In this research photodegradation of direct yellow dye using zinc oxide as catalyst under ultra-violet light has been investigated. The concentration of photocatalyst has been found to be 0.003 M, while the results reveal that, the best H2O2 concentration can be used as 10 ml, furthermore, pH to run the reaction of photodegradation was observed at acidic media. It has been found that the direct yellow dye can be oxidized by positive hole or hydroxyl radical or reduced by electron in the conduction band, the cleavage of N=N leads to break down the dye.